THE IMPACT OF DISEASES ON THE HUMAN PSYCHOLOGY - Olimov Saydullo Soxobjonovich (Ecominds Press, 2025)
Today, maintaining human health is one of the most important tasks. Finding the most effective ways to treat patients with oncological diseases and using them in practice is one of the main ideas of modern humanists.
Keywords: Oncology, prevention, treatment, lifestyle, patient, attitude